How can subnational governments develop and deliver distinctive policy agendas?. (December 2022) - Connell, Andrew; St Denny, Emily; Martin, Steve
The ways in which subnational governments develop and deliver distinctive policies is central to our understanding of effective multi-level governance systems. The existing literature focuses on institutional autonomy and the formal powers given to subnational governments but this is only one side of the story. Success also depends on the way in which policy actors deploy their powers, resources and legitimacy. This article presents an empirical analysis of two contrasting attempts to develop distinctive policy frameworks at the subnational level. It demonstrates the importance of looking beyond formal institutional powers and paying attention to policymakers' political skills and visibility, as well as the strategies and tactics that they employ in deploying formal powers. It highlights, in particular, the need for subnational governments to focus on those issues where they can make a difference and to exploit their nodality within policy networks to foster collaboration with state and non-state actors who bring complementary resources. Points for practitioners: A subnational government's success in pursuing distinctive policy agendas depends on the issues it decides to focus on and the way it chooses to deploy the formal powers and resources available to it. There is little point in investing time and efforts in pursuing issues that national governments are unwilling to cede control over. However, where they are given a degree of autonomy, subnational governments need to exploit their pivotal position in policy networks to foster collaboration with a range of state and non-state actors who bring complementary resources.